A taxonomy of tort law defences - Goudkamp, JLM (2009)
Tort law provides for a large number of defences to liability. While the circumstances in which some of these defences apply have been explored in detail, scant attention has been given to the theoretical foundations of defences. In particular, no serious attempt has been made to explain how defences relate to each other. This thesis seeks to reduce this gap in our understanding of tort law by proposing a system by which defences may be organised. It is argued that tort defences should be arranged into a threefold taxonomy consisting in (1) absent element defences; (2) justifications; and (3) public policy defences. These categories differentiate defences from each other on the basis of the story that they tell about the defendant’s practical reasoning. Absent element defences indicate that the defendant did not commit any wrong. Justifications reveal that the defendant acted wrongly but that his acts conformed to the balance of reasons. Public policy defences give no insight as to the quality of the defendant’s practical reasoning.